Solitary Intrathyroid Metastasis Occurring 23 Years after Resection of Renal Cell Carcinoma - X. Vandemergel (Case Reports in Endocrinology)
A case of solitary intrathyroid metastasis is described in a 60-year-old male patient. He had a history of renal cell carcinoma classified as T1b resected 23 years earlier. A mass was palpable in the right thyroid lobe. Ultrasound showed a hypoechoic polylobular nodule with intense vascularisation in the right lobe. Fine needle aspiration cytology was normal, but thyroidectomy was performed due to mass enlargement, the ultrasound pattern, and the oncological history. Histological examination revealed the presence of an intrathyroid metastasis of renal cell carcinoma. The bone scan and thoracoabdominal CT scan were normal. Postoperative care was uneventful.